Construction of a cuproptosis-associated lncRNA prognostic signature for bladder cancer and experimental validation of cuproptosis-related lncRNA UBE2Q1-AS1 - Shen, Junlin; Du, Mingyang; Liang, Shuang; Wang, Linhui; Bi, Jianbin (Frontiers in Medicine, 2023)
Copper levels are significantly altered in patients with thyroid, breast, lung, cervical, ovarian, pancreatic, oral, gastric, bladder, and prostate cancers. Outcomes can be predicted by constructing signatures using lncRNA-related genes associated with outcomes. We identified lncRNAs related to outcomes, those differentially expressed in bladder cancer, and cuproptosis-related lncRNAs from TCGA. We identified the intersection to obtain 12 genes and established a prognostic risk signature consisting of eight genes using LASSO-penalized multivariate Cox analysis. We constructed a training set, performed survival analysis on the high-and low-risk groups, and performed validation in the test and full sets. There existed a substantial contrast in the likelihood of survival amongst the cohorts of high and low risk. Univariate survival analysis of the eight genes showed that each gene distinguished between high-and low-risk groups. Sub-group analysis revealed that our risk score differed significantly in tumor stage, age, and gender. An in-depth analysis of the gene mutations associated with tumors was conducted to evaluate the risk of developing cancer. The results indicated a significant difference in the tumor mutation burden (TMB) between the low-and high-risk groups, which had a direct impact on the outcomes. These findings highlight the importance of TMB as a potential prognostic marker in cancer detection and prevention.We analyzed the immune microenvironment and found significant differences in immune function, validation responses, immunotherapy-related positive markers, and critical steps in the tumor immunity cycle between the high-and low-risk groups. We conducted an in-depth study of the immune checkpoints PD-1 and CTLA4 and found that the effect of anti-CTLA4 and PD-1 was higher in the high-risk group than in the low-risk group. Gene analysis of neoadjuvant chemotherapy revealed that the treatment effect in the high-risk group was better than in the low-risk group. We established a signature consisting of eight genes constructed from cuproptosis-related lncRNAs that have potential clinical applications for outcomes prediction, diagnosis, and treatment. This is a provisional file, not the final typeset article 1 UCSC Xena database (https://xena.ucsc.edu/).